GIS tools in the visualisation of a local spatial management plan - Ewa Debińska; Kamil Maciuk (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: The main objective of the study was to analyse the possibility of using GIS tools for 3D modelling of data presented on local spatial development plans (LSMP), with the view to maximising the use of planning provisions.